THE INFLUENCE OF THE WORKING ENVIRONMENT ON EMPLOYEE PERFORMANCE IN CLASS II PUBLIC INSTITUTIONS (LAPAS) BANGKO - ANGGARA BRATAMA; ERIANJONI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
The problem that occurs in Bangko Class II Correctional Institution (Lapas) is that the working environment in Bangko Class II Correctional Institution (Lapas) is still not good so that it can reduce employee performance. The work environment in question is a physical and non-physical work environment. The purpose of this study was to analyze the effect of the work environment on employee performance in Bangko Class II Correctional Institutions (Lapas). This study uses a quantitative approach. The study population consisted of 55 employees in Bangko Class II Correctional Institutions (Lapas). The sample in this study was determined through a total sampling technique so that the total sample was also the same, consisting of 55 respondents. Data were collected through a questionnaire with a Likert scale measurement and analyzed using a simple linear regression technique.